Exploring the epistemological role of the decomposed S&P 500 signal components on the formation of investors' sentiment - Gojart Kamberi (UTMS Journal of Economics, 2023)
In this paper we address the question of whether the investor sentiment (optimism, neutrality, pessimism) and the decomposed S&P 500 signal components (irregularity, seasonality and trend) are dynamically, and Granger causally related on a temporal scale. The aim is to identify structural relationships between decomposed S&P 500 signal components and investors' sentiment that would defend our proposition that the formation of investors' sentiment has an epistemological nature, grounded on the epistemic properties of the decomposed S&P 500 signal components. The preliminary VAR and Granger causality results do indicate a dynamic unidirectional relationship between S&P 500 signal as a whole and investors' sentiment. While the secondary Granger causality results do indicate a bidirectional relationship between the decomposed S&P 500 signal components and investors' sentiment. These two results altogether suggest a structural relationship where the S&P 500 signal decomposition does have an epistemological role on the formation of investors' sentiment and vice versa investors' sentiment does impact the S&P 500 signal only on the level of its decomposed components, but not on the S&P 500 signal as a whole.
Keywords: G1; 330